Hepatitis B virus drug resistance in HIV-1-infected patients taking lamivudine-containing antiretroviral therapy - Pawinee Wongprasit (2018)
A cross-sectional study was conducted in HIV-1-infected patients receiving lamivudine-containing antiretroviral therapy (ART) to determine the prevalence and risk factors of hepatitis B virus drug resistance (HBV-DR). HBV DNA and HBV genotypic resistance test were performed. Patients were categorized into two groups: with and without HBV-DR. There were 84 patients with a mean age (standard deviation [SD]) of 42.2 (10.2) years and 77% were males. Median (range) duration of ART and lamivudine use was 46 (3-177) and 40 (3-140) months, respectively. Median (range) CD4 cell count was 352 (49-790) cells/mm3. Of all, 19 (23%) had HBV-DR with a median (range) HBV DNA of 2.56 × 107(2.54 × 103-11 × 107) IU/mL. In univariate analysis, there were no differences in age, gender, ART regimen, liver function test, anti-HBc antibody, anti-HCV antibody between the two groups. Patients with HBV-DR had a higher proportion of positive HBeAg (68.4% versus 3.8%, p < 0.001). In multivariate analysis, positive HBeAg (odds ratio [OR) 16.64; 95% confidence interval [CI], 3.31-83.60] and duration of lamivudine use [per 6-month increment, OR 1.24; 95% CI, 1.06-1.36] were significant risk factors for HBV-DR. All 19 patients with HBV-DR had lamivudine resistance with the mutations as follows: M204V/I (95%), L180M/A181T (95%), L80V/I (47%), V173L (32%), and N236T (21%). Of these, 95%, 84%, 84%, and 0% of patients had HBV-DR to telbivudine, entecavir, adefovir, and tenofovir, respectively. HBV-DR is common in HBV/HIV-1 coinfected patients receiving lamivudine-containing ART without tenofovir. Positive HBeAg and longer duration of lamivudine use are risk factors for HBV-DR. In addition to lamivudine resistance, cross-resistance to other anti-HBV drugs is also frequently observed. © Mary Ann Liebert, Inc.